Assessment of multi-air emissions: Case of particulate matter (dust), SO2, NOx and CO2 from iron and steel industry of China. (20th September 2019) - Sun, Wenqiang; Zhou, Yue; Lv, Jingxiang; Wu, Jianzhong
Abstract: Industrial activities are generally energy and air emissions intensive, requiring bulky inputs of raw materials and fossil fuels and emitting huge waste gases including particulate matter (PM, or dust), sulphur dioxide (SO2 ), nitrogen oxides (NO x ), carbon dioxide (CO2 ), and other substances, which are severely damaging the environment. Many studies have been carried out on the quantification of the concentrations of these air emissions. Although there are studies published on the co-effect of multi-air emissions, a more fair and comprehensive method for assessing the environmental impact of multi-air emissions is still lacking, which can simultaneously consider the flow rate of waste gases, the availability of emitting sources and the concentrations of all emission substances. In this work, a Total Environmental Impact Score (TEIS) approach is proposed to assess the environmental impact of the main industrial processes of an integrated iron and steel site located in the northeast of China. Besides the concentration of each air emission substance, this TEIS approach also combines the flow rate of waste gases and the availability of emitting sources. It is shown that the processes in descending order by the values of TEIS are sintering, ironmaking, steelmaking, thermal power, steel rolling, and coking, with the values of 17.57, 16.68, 10.86, 10.43, 9.60 and 9.27, respectively. In addition, a sensitivity analysis was conducted, indicating that the TEIS order is almost the same with the variation of 10% in the permissible CO2 concentration limit and the weight of each air emission substance. The effects of emitting source availability and waste gas flow rate on the TEIS cannot be neglected in the environmental impact assessment. Graphical abstract: Image 1081449 Highlights: Total Environmental Impact Score (TEIS) is proposed for multi-air emissions assessment. Emitting source availability and waste gas flow rate are considered in TEIS. TEIS of particulate matter, SO2, NO x and CO2 from an iron and steel site is calculated.